Health Care in Sri Lanka : What Can the Private Health Sector Offer? - Govindaraj, Ramesh; Navaratne, Kumari; Cavagnero, Eleonora; Seshadri, Shreelata Rao (World Bank, Washington, DC, 2014)
This review represents an attempt to bridge the significant knowledge gaps on the private health sector in Sri Lanka, and foster a dialogue on opportunities for collaboration between the government and the private sector. It accomplishes this through a systematic collection and analysis of primary and secondary data on the provision, financing, and regulation of health care services. On health service delivery, the review finds that the private sector: includes a range of providers; focuses primarily on curative and outpatient services rather than preventive services; is heavily dependent on the public sector for its supply of human resources; and is concentrated in urban areas. The quality of health care services in Sri Lanka in both the private and public sectors, while better than in most developing countries, still lags behind those in more advanced countries. There is also little systematic dialogue and collaboration between the public and private sectors. On financing, the review finds that private health expenditure is more than half of total health expenditure, mostly in the form of out-of-pocket payments by households, with clear implications for Sri Lanka's progression toward universal health coverage. On stewardship and regulation, there is a clear and urgent need to bridge the existing gaps in the legal and regulatory framework, and in the enforcement of health regulations applicable to the private sector, as well as to create an enabling environment for more effective private sector participation in the health sector. The review demonstrates that the private health sector in Sri Lanka is a growing force, due both to greater investment from private players as well as greater demand from the population. The review highlights areas where a more effective engagement with the private sector could ensure that Sri Lanka is able to offer its citizens universal access to good quality health service while also stimulating economic growth.